Consensus statement and recommendations on the treatment of COVID-19: 2021 update. Issue 1 (10th September 2021) - Ko, Hsin-Kuo; Yu, Wen-Kuang; Pan, Sheng-Wei; Chen, Wei-Chih; Yang, Kuang-Yao; Lin, Yi-Tsung; Wang, Fu-Der; Yang, Muh-Hwa; Chen, Yuh-Min; ,
Abstract : Many treatments including antiviral and non-antiviral drugs, and critical care are considered for the management of coronavirus disease 2019 (COVID-19). Practice recommendations need to be updated and graded according to the critical evaluation of rapidly emerging literature. In June 2020, Research Center for Epidemic Prevention—National Yang Ming Chiao Tung University formed a task group comprising infectious disease clinicians, pulmonologists, and intensivists with varied areas of expertise. The steering committee prioritized questions and outcomes. The keywords for the searches were COVID-19 and prone position, extracorporeal membrane oxygenation (ECMO), noninvasive positive pressure ventilation (NIPPV), remdesivir, lopinavir, hydroxychloroquine/chloroquine (HCQ/CQ), azithromycin, corticosteroid, tocilizumab, convalescent plasma therapy, and intravenous immunoglobin (IVIG). A systematic review of peer-reviewed literature was performed by the consensus panel. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used in assessing the certainty of evidence and making recommendations. The effects of COVID-19 treatments on mortality and clinical improvement were summarized in 11 tables, and GRADE was presented to define the strength and quality of evidence for recommendation. The consensus recommended that prone position implanted in COVID-19 patients with hypoxic respiratory failure (IIC), careful selection for the support of ECMO (IIB), NIPPV being feasible but a risk of staff contamination (IIC), remdesivir generally administered in mild-to-moderate COVID-19 patients (IA), the use of dexamethasone in critically ill COVID-19 patients (IA), and the use of tociliziumab in hospitalized severe/critical COVID-19 patient with elevated markers of systemic inflammation (IA). The consensus recommended against the use of lopinavir/ritonavir (IB), HCQ/CQ (IA), azithromycin (IA), convalescent plasma therapy (IA), and IVIG (IA). The inception of the consensus and task group has provided much-needed evidence of the efficacy and safety of various therapies for the management of COVID-19 patients, and make a description about the benefits and harms for most treatments.